Substantive Evidence of Initial Habitation in the Remote Pacific - Carson, Mike T. (Archaeopress, 2017)
At the Unai Bapot Site of the Mariana Islands, new excavation has clarified the oldest known instance of a residential habitation prior to 1500 B.C. in the Remote Pacific, previously difficult to document in deeply buried layers that originally had comprised near-tidal to shallow subtidal zones.